Analisis Strategi Dan Inovasi Dalam Program Kegiatan Untuk Meningkatkan Pemulihan Sektor Ekonomi - Elza Novemiyawati; Khairun Nisa (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to analyze the strategies and innovations contained in activity programs designed to accelerate the recovery of the economic sector. In this context, an in-depth analysis of the various strategies used and the innovations implemented in order to improve the performance and recovery of the economic sector was carried out. The research methods used include literature studies and analysis of primary data collected through interviews or surveys. It is hoped that the findings from this research will provide better insight into how strategy and innovation can influence the success of activity programs in recovering the economic sector.